PERFORMANCE EVALUATION OF A PLASTIC BOTTLE-BASED SUBSURFACE IRRIGATION SYSTEM - Adigun, Habeeb Adekunle; Othman, Mohammed Khalid; Igbadun, Henry Evonameh (FUDMA JOURNAL OF SCIENCES, 2024)
Several attempts have been made by researchers for an efficient and cost-effective means of applying irrigation water, since traditional Surface irrigation system is becoming unsustainable due to water shortage. Adoption of most of these systems have failed because sophistication in design and complexity in setup. The use of recycled plastic bottles (PB) is another attempt at achieving a less complex system, yet promoting reuse of spent PB. Experimental Plot was set up in Samaru-Zaria, for a Subsurface irrigation system using recycled PB perforated at the base and connected to network of pipes. Evaluation of the system was carried out to determine the orifice size, orifice depth and the type of fertilizer application with the best agronomic yield parameters in RCBD design with sixteen (16) treatments replicated three (3) times. The results show the treatment with 3mm orifice size buried to 10mm depth with inorganic fertilizer performs best. The use of PB is therefore recommended for use in subsurface system to promote low-cost, less complex yet very effective water saving irrigation system.